Pengaruh Media Tanam Dan Dosis Pupuk Kandang Kambing Terhadap Pertumbuhan Dan Hasil Tanaman Kunyit (Curcuma Domestica Val.): Kunyit, Media Tanam, Pupuk Kandang Kambing - Wutun, Maria Magdalena Beto; Ratna Nurhayati, Dewi; Nikmatu Sholihah, Efi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
This study assessed the impact of goat manure on the growth and productivity of turmeric (Curcuma domestica Val.) plants in the Experimental Garden of the Faculty of Agriculture, Unisri, Surakarta, Central Java, from April to July 2024. The objectives of the study were to find the optimal planting media composition for turmeric growth and evaluate the effects of manure dose and planting media variation. The research design used a factorial completely randomized design (CRD) with two components. The first component consisted of four types of planting media: M0 (control soil), M1 (soil & rice husk), M2 (soil & rice husk charcoal), and M3 (soil & cocopeat). The second component is the dose of goat manure (K): K0 (0 g/plant), K1 (150 g/plant), K2 (200 g/plant), and K3 (250 g/plant). Data were analyzed by ANOVA and BNJ test at 5% significance level. This research gives results in the form of 1) Planting media has a significant effect on the wet weight of rhizomes, but has no effect on the number of leaves, the number of buds, and the wet weight of stems. 2) All variables were significantly affected by goat manure treatment. 3) The number of leaves, number of buds, and wet weight of stalks were also significantly affected by the interaction between treatments, while the wet weight of stalks was not affected.